Sorghum and millets : chemistry, technology, and nutritional attributes - Taylor, John R. N.; Duodu, Kwaku G. (Woodhead Publishing is an imprint of Elsevier, 2019)
'Sorghum and Millets: Chemistry, Technology and Nutritional Attributes, Second Edition, ' is a new, fully revised edition of this widely read book published by AACC International. With an internationally recognized editorial team, this new edition covers, in detail, the history, breeding, production, grain chemistry, nutritional quality and handling of sorghum and millets. Chapters focus on biotechnology, grain structure and chemistry, nutritional properties, traditional and modern usage in foods and beverages, and industrial and non-food applications. The book will be of interest to academics researching all aspects of sorghum and millets, from breeding to usage. In addition, it is essential reading for those in the food industry who are tasked with the development of new products using the grains. Key Features: Updated version of the go-to title in sorghum and millets with coverage of developments from the last two decades of research; Brings together leading experts from across the field via a world leading editorial team; Published in partnership with the AACCI -- advancing the science and technology of cereals and grains. --